Grade Retention and Social Promotion Dichotomy - Jacobs, Jeanette; Mantiri, Oktavian (8ISC Abstract Proceedings, 2022)
The dichotomy of retention versus promotion in education is persistent. It is a high stake decision teachers, administrators, and policymakers have to make. This article reviewed the die-hard factors of retention and looked at alternative ways to deal with them. Further, it emphasizes the importance that the approach towards repeating grades cannot be taken frivolously. Teachers, administrators, and policy makers’ decisions will not only have life-long effects for the individuals upon whom they are placed, but they will undoubtedly affect the future societies as a whole. This article suggested that both teachers and administrators have the vital and deciding power to elect which approach to take, that is, contextualizing curricula and professional development training that are sensitive to grade retention issues. Essential questions to ask are, is it possible to individualize the standards as opposed to group standards? Would doing away with grade levels work? Would professional development training create better learning environments that recognize and address individual student needs? Would frequent progress feedback to both parents and the student help? These are vital questions teachers, administrators, and policymakers must address to solve this dichotomy in the school’s locale as well as a regional milieu. We must have the insight to recognize our failures and the courage to accept new ways to deal with old problems. Keywords : Grade retention, social promotion, at-risk students, progress monitoring, failing students